(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the function of toponyms—or place names—in English-language tourism materials. It emphasizes how toponyms serve as tools of identity and storytelling, enhancing the cultural, historical, and geographical appeal of destinations. The study highlights that the strategic use of place names can strengthen destination branding and foster a closer connection between tourists and the places they visit.